2019
DOI: 10.1042/bsr20181450
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNAH11 gene polymorphisms with asthenozoospermia in Northeast Chinese patients

Abstract: Summary: Reduced or no progressive sperm motility in the fresh ejaculate defines asthenozoospermia as one of the major causes of male infertility. The axonemal heavy chain dynein type 11 (DNAH11) gene encodes for one of the axonemal dynein heavy chain (DHC) family members and participates in assembling respiratory cilia and sperm flagella. Given the high degree of conservation of DNAH11, mutations could give rise to primary ciliary dyskinesia (PCD) and asthenozoospermia. To date, few studies have reported on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…About 35–60% of MMAF infertility cases are associated with a genetic etiology, and MMAF has been reported to be associated with a variety of genes in humans and in mice [ 9 ]. In previous studies, several gene-families were identified to be associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the AKAP family, AKAP3 and AKAP4 mutations were identified causing dysplasia of the fibrous sheath, presenting MMAF phenotypes and male infertility [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 35–60% of MMAF infertility cases are associated with a genetic etiology, and MMAF has been reported to be associated with a variety of genes in humans and in mice [ 9 ]. In previous studies, several gene-families were identified to be associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the AKAP family, AKAP3 and AKAP4 mutations were identified causing dysplasia of the fibrous sheath, presenting MMAF phenotypes and male infertility [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic origin accounts for 35–60% of these MMAF cases. Several gene-families are identified as associated with flagella, including the AKAP family, DANI family, DNAH family, RSPH family, CCDC family, CFAP family, TTC family, and some single genes [ 1 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DNAH11 gene, mapped to chromosome 7p15.3, comprises 82 exons spanning over 358 kb and yielding a 14 kb mRNA 37,48 . DNAH11 protein, a member of the dynein heavy chain family, is involved in the composition of the axonemal dynein complex, which transforms energy into mechanical force, submits it to the microtubule and generates power to move the cilia and sperm flagella 19,49 . Some KS or PCD male patients may suffer from asthenozoospermia 50 .…”
Section: Discussionmentioning
confidence: 99%
“…37,48 DNAH11 protein, a member of the dynein heavy chain family, is involved in the composition of the axonemal dynein complex, which transforms energy into mechanical force, submits it to the microtubule and generates power to move the cilia and sperm flagella. 19,49 Some KS or PCD male patients may suffer from DNAH11 is composed of 4516 amino acids with the important globular head or motor domain. An N terminus, six ATPases associated with diverse cellular activity domains (AAA domains), a microtubule-binding region, two coiled-coil segments and a C terminus constitute the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation